Optimizing the Use of the AVIS System in Driving License Theory Test Services during the Covid-19 Pandemic by the Bandung Traffic Police - Satrio Bagaskara Gunadi Putra (Advances in Police Science Research Journal, 2021)
The increase in new vehicle users in the city of Bandung resulted in an increase in the number of SIM applicants at the Bandung Police Traffic Unit. Meanwhile, during the Covid-19 pandemic, SIM services at the Bandung Polrestabes Satlantas experienced limitations, due to the implementation of the Covid-19 Pandemic Health Protocol. The capacity of the SIM Theory Test Room at Satlantas Polrestabes Bandung can only accommodate 15 SIM Theory Test participants for 1 (one) period out of 30 tables/PCs available. This makes it a challenge for the Bandung Police Satlantas. The author is interested in knowing how to use the AVIS System in SIM Theory Test services during the Covid-19 Pandemic, what are the factors that influence the issuance of the AVIS System SIM during the Covid-19 Pandemic, and how to optimize the use of the AVIS System in SIM Theory Test services during the Covid Pandemic. -19 by Satlantas Polrestabes Bandung. The research method uses descriptive analysis with a qualitative approach, as well as data collection techniques by interviewing, observing, and reviewing documents. Study the problem using the Public Service Standards (Kemenpan), the Concept of Excellent Service and the Dimensions of Service Quality. The study found that the use of the AVIS System in the SIM Theory Test service at the Bandung Police Traffic Unit during the Covid-19 Pandemic was less than optimal, causing longer queues than before the pandemic, There are internal and external factors that affect the optimization of the use of the AVIS System in SIM Theory Test services, The optimizations that have been carried out such as adding an outdoor waiting room, providing an enlightenment room and enlightenment books and making the entry/exit flow of the SIM Theory Test room have not been able to make it Optimal. Suggestions for optimization are the use of the Android-based AVIS system, the dual function of the Enlightenment Room and the SIM Theory Test Room, the need for further research on the use of the android-based AVIS system, the need for coordination of the Korlantas regarding SOPs for the use of android, budgeting, wasdal leadership, and cooperation with the Dikyasa Unit for socialization.